Effect of solution treatment and aging period on Magnesium sacrificial anode in backfill and soil environment - Rogemah Ramli (Universiti Malaysia Perlis, 2008)
Magnesium anode is one of the materials that applied as sacrificial anode. In this study, high potential magnesium anode (HPMA) was used as a test sample. The main objective of this project was to evaluate the effect of heat treatment magnesium anode when immerse in backfilled and soil environment. There are two different parameters of heat treatment applied on this study. The first solution treatment parameter was carried out at 300ºC for 14, 30 and 54 hour before all the sample were aged at 150º C for 24 hours. While, the second parameter was done at 300°C for 6 hours solution treatment before it was aged 150°C for 8, 24 and 48 hours. The sample was then immersed in the backfilled and soil environment for one month period. It was found that weight loss occurs and it believes resulted by reduction of Mg ions and pit growth. Corrosion rate of magnesium anode was found no significant different in form of heat treatment period. Corrosion rate of the sample decrease with the increasing immerse period. Pitting depth of the magnesium anode was observed propagate in the direction of gravity.